Social Media Exposure towards Asian Youth Smoking Behaviour: A Scoping Review - Sella Puspita Sari; Swatitis Kurnia Saputri, Meylida; Budi Mustofa, Syamsulhuda; Nurjazuli (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Smoking habits among teenagers have a significant impact on public health. Smoking in adolescence is a global health problem that requires serious attention because it can have long-term impacts on public health, including an increased risk of chronic diseases in later life. Aims: This review aims to identify the influence and impact of cigarette promotion on social media on adolescent smoking behavior in Asia. Method: This research uses a scoping review method to explore and understand the level of cigarette consumption among teenagers in various Asian countries. Search using Pubmed, Google Scholar, and Springer Link databases. Search for articles using the main keywords Asian youth cigarette consumption, influence and impact. This review was conducted on 200 articles that were screened and a total of 10 articles were analyzed. The selected articles are in English and Indonesian, with a period of five years between 2019 and 2024. Types of articles cover the fields of medicine, health, health care, environmental science, and social science. The types of documents used are journals and articles with full text and free. The articles come from Germany, England, the United States, Malaysia, China, Taiwan, and Indonesia. Results: The results of this study indicate that cigarette promotion on social media can have a significant influence on smoking behavior among youth in Asia. Conclusion: We have identified that cigarette promotion on social media influences adolescent smoking behavior due to low self-efficacy, peers, ineffective promotional advertising, and family habits.